A rare case report of the left side hydrocele with scrotal calculi (Indian Journal of Case Reports, 2020)
Scrotal calculi correspond to the presence of freely floating or located calcifications lying between the layers of the tunica vaginalis of the testes. In the hydrocele fluid, scrotal calculi are found incidentally during ultrasound, operation, or clinical if large in size. A 60-year-old man presented with a left scrotal swelling. He had a history of mild pain while walking. Physical examination of the patient revealed a 12 cm × 8 cm cystic, fluctuant, transilluminate swelling without cough impulse. In ultrasonography, it was suggestive of free fluid with fine internal echo in the left tunica. After incising the tunica vaginalis, evidence of 250 mL of an amber-colored fluid was evacuated and a small round, 0.5 cm sized. The patient recovered well and the post-operative period was uneventful. If the stone is adherent to the tunica albuginea and does not change position on ultrasonography, the possibility of a tumor has to be in mind.